Investigating the motivational behavior of pupils during outdoor science teaching within self-determination theory - Dettweiler, Ulrich; Ünlü, Ali; Lauterbach, Gabriele; Becker, Christoph; Gschrey, Bernhard (Frontiers in Psychology, 2015)
This paper presents data from a mixed-method pilot study (n=84) searching into learning psychological aspects of an outdoor science teaching programme. We use data from qualitative explorations into the pupils’ learning motivation during field observation, a group interview, and open questionnaires, in order to understand quantitative measures from the Self-Determination Index (SDI), and the Practical Orientation (PO) of the programme. Our data suggest that lower self-regulated pupils in “normal” science classes show a significantly higher self-regulated learning motivational behaviour in the outdoor educational setting (p<10^-4), and that the outdoor-teaching has generally been perceived as more practical than teaching at the normal school context (p<10^-4), irrespective of gender or school culture. We are going to provide in-depth analyses of all quantitative findings with our qualitative data and thus explain the findings logically, with respect to the direction of the statistical interpretation, and substantially, with respect to the meaning of the discoveries. We conclude that outdoor programming appears to be a suitable tool to trigger interest in science in youngsters, especially for less motivated pupils.